TM LDH Meets Birnessite: A 2D‐2D Hybrid Catalyst with Long‐Term Stability for Water Oxidation at Industrial Operating Conditions. (17th March 2021) - Chen, Zhuwen; Ju, Min; Sun, Mingzi; Jin, Li; Cai, Rongming; Wang, Zheng; Dong, Lei; Peng, Luming; Long, Xia; Huang, Bolong; Yang, Shihe
Abstract: Efficient noble‐metal free electrocatalyst for oxygen evolution reaction (OER) is critical for large‐scale hydrogen production via water splitting. Inspired by Nature's oxygen evolution cluster in photosystem II and the highly efficient artificial OER catalyst of NiFe layered double hydroxide (LDH), we designed an electrostatic 2D‐2D assembly route and successfully synthesized a 2D LDH(+)‐Birnessite(−) hybrid. The as‐constructed LDH(+)‐Birnessite(−) hybrid catalyst showed advanced catalytic activity and excellent stability towards OER under a close to industrial hydrogen production condition (85 °C and 6 M KOH) for more than 20 h at the current densities larger than 100 mA cm −2 . Experimentally, we found that besides the enlarged interlayer distance, the flexible interlayer NiFe LDH(+) also modulates the electronic structure of layered MnO2, and creates an electric field between NiFe LDH(+) and Birnessite(−), wherein OER occurs with a greatly decreased overpotential. DFT calculations confirmed the interlayer LDH modulations of the OER process, attributable to the distinct electronic distributions and environments. Upshifting the Fe‐3d orbitals in LDH promotes electron transfer from the layered MnO2 to LDH, significantly boosting up the OER performance. This work opens a new way to fabricate highly efficient OER catalyst for industrial water oxidation. Abstract : A 2D‐2D hybrid catalyst with advanced activity and long‐term stability toward water oxidation under industrial alkali hydrogen production conditions is reported, which solves the instability problem of LDH and the low activity of Birnessite together. The modulated electronic structure of all transition metal ions with perfect linear correlation to electron transfer as well as the built‐in electric field of the hybrid catalyst has been revealed.